Critical perspectives on resistance in 21-st century British literature - Ayyildiz, Nilay Erdem (Cambridge Scholars Publishing, 2024)
This book sets out on an intellectual journey, with each chapter acting as a unique compass to lead the reader through the critical perspectives on resistance waiting to be discovered in 21st-century British literature. As such, the book appeals to general readers, including undergraduates, researchers, professionals and anyone who is interested in cultural studies, literary studies, the humanities and sociology, particularly resistance and discourse studies.